2019
DOI: 10.3390/ma12101574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Copper-Based Alloy (C93200) Composites Reinforced with Marble Dust Developed by Stir Casting under Vacuum Environment

Abstract: Copper-based alloy (C93200) composites reinforced with a different weight percentage of marble dust particles (1.5, 3, 4.5, and 6 wt.%) were developed by stir casting method under vacuum environment. By using this type of reinforcement, it was possible to detect a suitable material for bearing applications. The manufactured material was characterized for its mechanical properties using a micro-hardness tester. A universal INSTRON-5967 machine was used to detect the yield and tensile strength. Further the hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A similar trend was seen in study of Rajak et al., which showed that MD addition decreases wear rate in copper alloy-based composites. 11 Figure 7 describes the influence of MD addition on the PDC-9 (wear rate at 5 N), PDC-10 (wear rate at 15 N), PDC-11 (wear rate at 25 N) and PDC-12 (wear rate at 35 N) of the developed bearing materials. It was observed from Figure 7 that the specific wear rate decreased continuously with increasing normal loading from 5 N to 25 N. With increase in loading value and MD addition, the actual contact surface area increases causing the reduction in applied load between the two contacting surfaces and thus the specific wear rate was decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was seen in study of Rajak et al., which showed that MD addition decreases wear rate in copper alloy-based composites. 11 Figure 7 describes the influence of MD addition on the PDC-9 (wear rate at 5 N), PDC-10 (wear rate at 15 N), PDC-11 (wear rate at 25 N) and PDC-12 (wear rate at 35 N) of the developed bearing materials. It was observed from Figure 7 that the specific wear rate decreased continuously with increasing normal loading from 5 N to 25 N. With increase in loading value and MD addition, the actual contact surface area increases causing the reduction in applied load between the two contacting surfaces and thus the specific wear rate was decreased.…”
Section: Resultsmentioning
confidence: 99%
“…4.5 wt.%), the coefficient of friction and wear performance improves considerably. 11 Gangwar et al. fabricated quicklime (CaO) reinforced silicon-bronze alloy composites by varying the weight percentages as 0, 2.5, 5, 7.5 and 10 for bearing material employing high temperature vacuum casting machine.…”
Section: Introductionmentioning
confidence: 99%
“…MD reinforcement of 4.5 wt % was chosen as the best alternative automotive application. 37 The automobile elements consist of rotating machine parts involving effective utilization of rolling element bearings. The inappropriate selection of materials may result in the failure of bearings that can further increase the cost and lead time.…”
Section: Automotive Applicationsmentioning
confidence: 99%
“…The decrease in wear loss (improved wear performance) is attributed to an adequate reinforcement bonding between the copper matrix alloy and hard marble dust particles that resulted in higher hardness of composites. 37 Ray et al studied the wear behavior of glass epoxy hybrid composite reinforced with varying weight percent values (0, 5, 10, 15 wt%) of MD. With the help of Taguchi experimental trials and ANN prediction, it was found that there is a strong correlation between different control factors and erosion wear behavior, and optimal settings was predicted for minimum wear loss.…”
Section: Effect Of Marble Dust On Tribological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation